Assessing Emotional Intelligence among Dental Undergraduate Students: An Institutional Insight from Western India in the Postpandemic Context - Nivedhitha Maraimalai; Tabita Joy Chettiankandy; Akshay Chandrakant Trimukhe; Saumya Tiwari; Chein Chai Aaron Yen (Wolters Kluwer Medknow Publications, 2024)
Background Emotional intelligence (EI) plays a pivotal role in academic success, especially in challenging fields such as dentistry. The COVID-19 pandemic has revolutionized education, necessitating a fresh examination of EI among dental students in the postpandemic era. Materials and Methods This cross-sectional study involved undergraduate dental students and employed a structured questionnaire comprising 21 questions to assess EI, gather demographic data, and explore learning behaviors. The gathered data underwent rigorous statistical analysis using SPSS, including Chi-square tests. Results Among the 525 students, 168 participated, representing a 32% response rate. Notably, the majority of respondents were female (67%) and exhibited EI scores predominantly in the moderate range. Significantly, the study revealed noteworthy correlations between EI and family income (P = 0.03*) and study hours (P = 0.00*). However, no substantial link was identified between EI and work completion behavior. Discussion This study illuminates the intricate relationship between EI, socioeconomic factors, and study habits within the context of dental education. It implies that greater family income and increased study hours positively influence EI. The practical implications extend to tailored EI programs and addressing educational disparities. Conclusion This study significantly advances our comprehension of EI among dental students. It underscores the relevance of EI in dental education and advocates for equitable educational strategies in a post-COVID landscape.